PENGARUH RUBRIK FASHION MAJALAH GOGIRL! TERHADAP PERILAKU MENIRU TREND FASHION DI KALANGAN MAHASISWI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Ardilla, Sucie Nella; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Most of university liberate their students to dress in the collage. Of course with the applicable rules. But along with times many changes happened in dress. We can found a lot of trends that look unusual and eccentric. On the other hand, Fashion magazine looks more incentives to providing the latest fashion trends. Each magazine provides its own fashion style according to the age category in that magazine. And the GoGirl! magazines, included in the category of magazines that read by the students. This is what eventually became the purpose of the study, researchers wanted to determine whether there is influence of fashion rubric GoGirl! magazine to imitate the behavior of a fashion trend among the student of the Faculty of Social and Political Sciences.The method used in this research was quantitative method with explanatory survey, researchers collected data using questionnaires. The location of this research was in the Faculty of Social and Political Sciences, University of Riau. The number of samples for this researchers were 229 respondents, sampling using stratified random sampling technique. To determine how much influence these two variables, the researchers used a simple linear regression analysis. As for the questionnaire data processing, performed using Statistics Program Product Of Service Solutions (SPSS) version 20 windows.The results of this study indicated that the influence of fashion rubric GoGirl! magazine to imitate the behavior of a fashion trend among the student of the Faculty of Social and Political Sciences, University of Riau, regression coefficient values obtained in this study is Y = 3.617 + 0344 X with a significance level of 0.000 is smaller than α = 0.05. This suggests there is influence of fashion rubric GoGirl! magazines to imitate the behavior of the fashion trend of 41% with moderate category, meaning that mimics the behavior of the fashion trend of the fashion magazine section GoGirl! Pretty much. This is because women still find references benyak fashion of serving a variety of fashion magazines. The remaining 59% is influenced by other variables outside of this researchKey words : S-O-R Theory, Magazine,Students, University of Riau